The practice of imposing administrative fines by the State Data Protection Inspectorate in the context of other EU Member States - Šidlauskas, Aurimas (Socialiniai tyrimai, 2021)
The implementation of the EU General Data Protection Regulation (hereinafter referred to as the Regulation), which, among other things, aims to eliminate disparities between national systems and to alleviate unnecessary administrative burdens, began on 25 May 2018. Each Member State is to ensure that there is one or more independent public authorities (hereinafter referred to as the supervisory authority) responsible for monitoring the implementation of the Regulation. In Lithuania, personal data protection is supervised by two authorities, namely by the State Data Protection Inspectorate (hereinafter referred to as the SDPI) and by the Office of the Inspector of Journalist Ethics. The powers conferred on the supervisory authorities by the Regulation are greater and broader in scope than those granted under previous data protection legislation. Organizations which process personal data must ensure compliance with the requirements laid down in the Regulation. A supervisory authority that violates the provisions of the Regulation may be faced with heavy administrative fines and other sanctions. This article analyzes the practice of imposing administrative fines in the EU and in Lithuania as compared to other EU Member States. The author of the article believes that evaluating the practice of imposing administrative fines by the SDPI within the general context of the EU shall enable one to search for the reasons behind the current situation, as well as to improve the processes the SDPI employs to perform functions associated with data protection supervision. The article uses generalization and comparative analysis of scientific literature, legal documents and statistical data.